Design and Application of Fluid Pump Drainage Gas Recovery Technology in Dongsheng Gas Field - Zhou Ruili; Luo Yi; Qiao Qianyu; Wu Weiran; Yang Feishan; Zhao Rundong; Xue Zhaoyang (Shiyou jixie)
To effectively address the bottleneck problems of high injection pressure and high energy consumption of hydraulic jet pump technology， it is urgent to improve and optimize the drainage gas recovery technology of high water-production gas wells. First， based on the design principle of Venturi effect， the fluid pump technology using gas as jet medium was adopted to efficiently activate the production capacity of medium and low-pressure high water production gas wells and improve the technology adaptability. Second， Well Q1 was selected to conduct application evaluation of fluid pump technology. The study results show that the fluid pump technology only needs 5–7 MPa pressure to realize normal cleanup， the production time rate is up to 98.4%， the liquid withdrawal capacity is 18.42 times higher than that of single well rotative gas lift technology， and the daily liquid flow rate is 13.1 times higher than that of the electric valve intermittent opening technology. In addition， it does not need the assistance of foam-aided drainage gas recovery technology. Compared with the jet pump technology， the pump pressure is only 20.6%–32.3% of the jet pump， and the daily average power consumption is only 34.6%–75.3% of the jet pump， fully verifying the effectiveness of low pressure and low energy consumption work of the fluid pump， and successfully solving the problem of high injection pressure and high energy consumption of hydraulic jet pump. The study results are of great significance for realizing continuous liquid-carrying gas production of gas wells and efficiently activating the production capacity of high water-production gas wells.